Sektor Unggulan dan Hubungannya dengan Ketenagakerjaan dan Kemiskinan di Provinsi Kalimantan Selatan - Listiawati, Listiawati; Siregar, Syahrituah (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to analyze the leading sectors in South Kalimantan Province, determine the relationship between the top sectors and employment, and the relationship between the leading sectors and poverty in South Kalimantan Province. The analytical tools in this research are Static Location Quotient (SLQ), Dynamic Location Quotient (DLQ), Esteban-Marquillas Shift Share, and Specialization Index. The Pearson Correlation Test determines the relationship between leading sectors and the dependent variable. Secondary data uses the 2016-2020 period. The results showed that the mining sector is the leading sector in South Kalimantan Province. The leading sector relationship to employment shows a unidirectional and significant relationship, assuming that the higher the mining sector's contribution to the total GDP, the higher employment will be. Meanwhile, the relationship between the leading sectors and the poverty level shows an opposite and significant relationship, assuming that the higher the mining sector's contribution to the total GRDP, the lower the percentage of people experiencing poverty will be.